ANALISIS DEIKSIS DALAM NOVEL TERJEMAHAN THE GREAT GATSBY KARYA F. SCOTT FITZGERALD - Salsabila, Asya Thalia; Rasdana, Oki (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
The aim of this research is to investigate the existence of deixis in the translated version of The Great Gatsby and explain the deixis contained in this novel. This research is included in the qualitative descriptive research category. The research methodology used in this study is a descriptive approach. The data collection techniques used in this research are reading and note-taking techniques. Then the data in this research was analyzed based on deixis theory by Levinson (1983). The data for this research was obtained directly from the novel The Great Gatsby by F. Scott Fitzgerald, which was translated by Maria Masniari Lubis. The results of this research reveal that the novel The Great Gatsby uses various forms of deixis, namely (1) personal deixis, which includes first person singular and plural personal deixis, second person singular and plural personal deixis, and third person singular and plural personal deixis, (2) time deixis, (3) place deixis, (4) discourse deixis, and (5) social deixis. The conclusion that can be drawn from this research is that the novel The Great Gatsby is dominated by the use of persona deixis.